Answer:
x = -
, x = -
Explanation:
6x² + 23x + 20 = 0 ( factorise the left side )
consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 6 × 20 = 120 and sum = 23
the factors are + 8 and + 15
use these factors to split the x- term
6x² + 8x + 15x + 20 = 0 ( factor the first/second and third/fourth terms )
2x(3x + 4) + 5(3x + 4) = 0 ← factor out (3x + 4) from each term
(3x + 4)(2x + 5) = 0
equate each factor to zero and solve for x
2x + 5 = 0 ⇒ 2x = - 5 ⇒ x = -
3x + 4 = 0 ⇒ 3x = - 4 ⇒ x = -